2020
DOI: 10.1111/his.14298
|View full text |Cite
|
Sign up to set email alerts
|

Non‐conventional dysplasia in inflammatory bowel disease is more frequently associated with advanced neoplasia and aneuploidy than conventional dysplasia

Abstract: Conclusions: Non-conventional morphological patterns of dysplasia are not uncommon in IBD, detected in 33% of the patients. The higher frequencies of advanced neoplasia (HGD or CRC) and aneuploidy in non-conventional dysplasia, in particular CCD, hypermucinous and GCD variants, suggest that they may have a higher malignant potential than conventional dysplasia or sporadic tubular adenomas, and thus need complete removal and/or careful follow-up.Greater than 40% of non-conventional dysplasia presented as a flat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
132
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(148 citation statements)
references
References 45 publications
12
132
1
Order By: Relevance
“…In support of this argument, we recently reported that nonconventional dysplasia (38%) is more frequently associated with advanced neoplasia than conventional dysplasia (19%) (p < .001) [38]. Notably, non-conventional dysplasia with low-grade morphology had a significantly higher rate of aneuploidy (46%) than low-grade conventional dysplasia (8%, p = .002) or sporadic adenomas (9%, p = .037).…”
Section: Potential Significance Of Non-conventional Dysplasiamentioning
confidence: 79%
See 4 more Smart Citations
“…In support of this argument, we recently reported that nonconventional dysplasia (38%) is more frequently associated with advanced neoplasia than conventional dysplasia (19%) (p < .001) [38]. Notably, non-conventional dysplasia with low-grade morphology had a significantly higher rate of aneuploidy (46%) than low-grade conventional dysplasia (8%, p = .002) or sporadic adenomas (9%, p = .037).…”
Section: Potential Significance Of Non-conventional Dysplasiamentioning
confidence: 79%
“…It is predominantly found in UC patients (86%) who often have a concurrent history of PSC (29%). Although the majority of hypermucinous dysplastic lesions have a polypoid endoscopic appearance with a mean size of 2.1 cm [38], up to 42% are endoscopically invisible or flat (unpublished results). Hypermucinous dysplasia shows a predilection for the left colon (57%).…”
Section: Hypermucinous Dysplasiamentioning
confidence: 93%
See 3 more Smart Citations